Efek Penerimaan Daerah Melalui Pertumbuhan Ekonomi Dalam Mempengaruhi Belanja Modal di Indonesia - Rahman, Abdul (Universitas Negeri Padang, 2025)
Capital expenditure plays a critical role in regional economic development, yet its effectiveness is highly influenced by the fiscal capacity of local governments. This study aims to analyze the effect of locally generated revenue, revenue-sharing funds, general allocation funds, and special allocation funds on capital expenditure in Indonesia, with economic growth as a mediating variable. A quantitative approach was employed using panel data regression analysis on 34 provinces in Indonesia from 2019 to 2023. The Fixed Effect Model (FEM) was selected based on Chow and Hausman test results. Path analysis was used to examine both direct and indirect effects between variables. The findings indicate that locally generated revenue and special allocation funds have a positive and significant impact on capital expenditure, while general allocation funds show a significant negative effect and revenue-sharing funds are statistically insignificant. Locally generated revenue and revenue-sharing funds positively influence economic growth, whereas special allocation funds have a negative effect. Economic growth does not significantly affect capital expenditure, thus it does not serve as a mediating variable. The study suggests optimizing local revenue and evaluating the effectiveness of general and special fund allocations. Future research should consider institutional and governance quality as additional explanatory variables.